Impedimetric Biosensors for Detecting Vascular Endothelial Growth Factor (VEGF) Based on Poly(3,4-ethylene dioxythiophene) (PEDOT)/Gold Nanoparticle (Au NP) Composites - Kim, Minsoo; Iezzi, Raymond; Shim, Bong Sup; Martin, David C. (Frontiers in Chemistry, 2019)
In advanced forms of diabetic retinopathy, retinal vascular occlusive disease and exudative age-related macular degeneration, vision loss is associated with elevated levels or extravasation of vascular endothelial-derived growth factor (VEGF) into the retina, vitreous and anterior chamber of the eye. We hypothesize that point-of-care biosensors, capable of rapidly and precisely measuring VEGF levels within the eye will assist clinicians in assessing disease severity and in establishing individualized dosing intervals for intraocular anti-VEGF injection therapy. An impedance biosensor based on a poly(3,4-ethylenedioxythiophene) (PEDOT)/gold nanoparticle (Au NP) composite was developed for detecting VEGF. PEDOT with Au NP was electrochemically deposited on three different medical electrode sensor designs: free-standing pads, screen printed dots, and interdigitated micro-strip electrodes. Anti-VEGF antibody was covalently immobilized on the surface of the polymer films through attachment to citrate-functionalized Au NPs, and the resulting composites were used to detect VEGF-165 by electrochemical impedance spectroscopy (EIS). The PEDOT-Au NP composite materials were characterized using optical microscopy, SEM/EDS, FIB, TEM and STEM techniques. Among the different micro-electrodes, the interdigitated strip shape showed the best overall film stability and reproducibility. A linear relationship was established between the charge transfer resistance (R_ct) and VEGF concentration. The detection limit of VEGF was found to be 0.5 pg/mL, with a correlation coefficient of 0.97  0.65%. These results indicate that the proposed PEDOT/Au NP composites can be used in designing low-cost and accurate VEGF biosensors for applications such as clinical diagnosis of VEGF-mediated eye disease.